Couple Adaptation to the Birth of a Child: The Roles of Attachment and Perfectionism. (31st August 2020) - Gingras, Anne‐Sophie; Lessard, Isabelle; Mallette, Frédéric; Brassard, Audrey; Bernier‐Jarry, Audrey; Gosselin, Patrick; de Pierrepont, Catherine
Abstract : This study aims to examine two explanatory factors of relationship satisfaction and parental alliance among both parents of a new child, namely romantic attachment and perfectionism. A sample of 80 couples completed individual online questionnaires. Path analyses based on the Actor‐Partner Interdependence Model were carried out to explore the actor and partner effects of each explanatory variable (attachment, perfectionism) on both partners' postnatal relationship satisfaction and parental alliance. Results revealed that attachment avoidance is negatively related to each partner's own relationship satisfaction and parental alliance, whereas attachment anxiety is related to their own lower parental alliance. Maladaptive perfectionism is negatively related to each partner's own relationship satisfaction, whereas adaptive perfectionism is positively related to each partner's own relationship satisfaction. These results extend the understanding of the factors contributing to parental and couple adaptation in the postnatal period. They highlight the role of attachment and perfectionism for improving postnatal professionals' interventions.